The Divine Wisdom and the Divine Economy - Nimmo, Paul T. (Modern theology, 2018)
This article offers an initial exposition of the divine perfection of wisdom, and proceeds by way of attention to and development of the apostolic witness to Jesus Christ found in Scripture. The first section offers a concise reflection on method, and outlines a path of inquiry that affords primary attention to the apostolic proclamation of Jesus Christ. The second section outlines the contours of an account of the divine wisdom derived in this way. From this perspective, light is shed on the relationship between the divine wisdom and the divine acts of creation and providence. The final section briefly considers the implications of pursuing this trajectory into theology proper, that is, its possible implications for the doctrine of God.